2020
DOI: 10.1371/journal.pone.0230020
|View full text |Cite
|
Sign up to set email alerts
|

Renal resistive index in chronic kidney disease patients: Possible determinants and risk profile

Abstract: BackgroundHigh ultrasound renal resistive index (RI) predicts poor cardiorenal outcomes in chronic kidney disease (CKD) and has recently emerged as a marker of nephroprotective drugs response. Thus, having a risk profile of CKD patients with abnormal RI may be relevant for the clinicians. MethodsConsecutive patients referred to our non-dialysis CKD clinic from 01/01/2016 to 01/12/2016, were evaluated by clinical and ultrasound analysis. Inclusion criteria were age >18 years and presence of CKD defined as estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 55 publications
5
23
1
Order By: Relevance
“…In the present study, it was revealed that heart rate showed association with KB concentration, while cases with high-normal levels of KBs had the lowest risk of increased PSV, and those with middlenormal levels of KBs had the lowest risk of increased RI [35]. Moreover, RI is not only a risk factor of glomerular and tubular damage and kidney disease progression but also a marker of endothelial dysfunction [36]. The results of the present study were not consistent with those reported previously, due to the following reasons.…”
Section: Discussionsupporting
confidence: 45%
“…In the present study, it was revealed that heart rate showed association with KB concentration, while cases with high-normal levels of KBs had the lowest risk of increased PSV, and those with middlenormal levels of KBs had the lowest risk of increased RI [35]. Moreover, RI is not only a risk factor of glomerular and tubular damage and kidney disease progression but also a marker of endothelial dysfunction [36]. The results of the present study were not consistent with those reported previously, due to the following reasons.…”
Section: Discussionsupporting
confidence: 45%
“…Evidence is also emerging for a possible role of the renal resistive index (RRI) as a dynamic predictive biomarker. RRI is a Doppler ultrasonographic index, whose increase reflects both renal and systemic vascular impairment [105]. RRI was also found to predict the onset of CV and kidney outcomes in patients with CKD or essential hypertension [106,107].…”
Section: Ultrasound Biomarkersmentioning
confidence: 99%
“…Raised RI levels above have been shown to reflect renal and systemic vascular impairment and predict CV events in hypertensive and CKD patients [105][106][107]. Medications as RAAS inhibitors and SGLT2-i reduce RRI levels over time and improve vascular damage [108,109].…”
Section: Rrimentioning
confidence: 99%
“…To provide more insights into individual variability in drug response, the “ideal” path to follow is to find out the mechanism of damage in each individual and to find the drug that can significantly influence that mechanism, thus pursuing a targeted treatment approach. The progress obtained by “omics,” namely, novel techniques used to analyze molecular processes associated with the disease (genomics, proteomics, metabolomics, and transcriptomics) will likely allow the discovery of novel pathways of damage and consequently potential targets for therapeutic interventions [71, 91]. Genome-wide association studies identified the variants of the UMOD gene that cause overexpression of uromodulin and upregulation of the tubular transporter NKCC2.…”
Section: Precision Nephrology In Intervention Studies: Reducing Variamentioning
confidence: 99%